Cross-sectional and longitudinal associations between self-esteem and BMI depends on baseline BMI category in a population-based study - Margaux Robert; Benjamin Allès; Ulrike A. Gisch; Rebecca Shankland; Serge Hercberg; Mathilde Touvier; Christophe Leys; Sandrine Péneau (BMC, 2024)
Abstract Background Some studies have reported associations between self-esteem and weight status, but longitudinal data on adults remain scarce. The aim of this population-based study was to analyze the cross-sectional and longitudinal association between self-esteem and body mass index (BMI) and to investigate whether baseline BMI has an impact on this association. Methods In 2016, 29,735 participants aged ≥ 18 years in the NutriNet-Santé cohort completed the Rosenberg Self-Esteem Scale. BMI was self-reported yearly over a 4-year period. Association between self-esteem and BMI was assessed using mixed models and logistic regressions. Analyses were stratified by BMI (categorical) at baseline and adjusted on sociodemographic and lifestyle characteristics. Results At baseline, higher self-esteem was associated with higher BMI in normal weight individuals(p = 0.32), and with lower BMI in obese class II and III individuals (p = 0.13). In addition, higher baseline self-esteem was associated with BMI increase over time in normal weight individuals (p = 0.15). Among normal weight individuals, those with higher self-esteem were less likely to show a decrease in their BMI (p = 0.005), while no association was observed with BMI increase (p = 0.81). Discussion Our findings suggest that the association between self-esteem and BMI depends on the initial category of BMI, with a negligible effect of self-esteem.